(N|LEKTRONIKA BOLX[IH MO]NOSTEJ I FIZIKA PLAZMY (B:s (NnAU^NYE TRUDY (B/s - (NkAPICA(B, (NpETR lEONIDOWI^s ((NmOSKWA (B:s (NnAUKA(B,s, 1991)
(NbIBLIOGR(B. (NW KONCE ST(B.s
(NuKAZ(B. (NIMEN(B: (NS(B. 401s
(Nan sssr(B, (NiN(B-(NT FIZ(B. (NPROBL(B. (NIM(B. (Np(B. (Nl(B. (NkAPICYs
Keywords: (NgENERATORY SWERHWYSOKO^ASTOTNYEs; (NpLAZMA (B((NFIZ(B.)s